Analysis of kombucha antioxidant activity with variations in percentage of pomegranate extract (Punica granatum) and fermentation time: Analisis aktivitas antioksidan kombucha dengan variasi persentase sari delima (Punica granatum) dan lama fermentasi - Metha Putri Agustyn Anggraini; Merkuria Karyantina; Yannie Asrie Widanti (Fakultas Sains dan Teknologi Unisri, 2025)
Kombucha is one of the processed products of fermented sugar and tea with a starter mixture ofkombucha culture called SCOBY (Symbiotic Cultures of Bacteria and Yeast). Kombuchafermentation is carried out using yeast and bacteria microorganisms. Pomegranate or often calledpomegranate is a fruit that has quite high antioxidants. The purpose of this study was to determinethe characteristics of pomegranate juice kombucha with variations in concentration andfermentation time which have high antioxidant activity. This study used a factorial randomizeddesign with two factors and two repetitions. The factors used were variations in the percentage ofpomegranate juice (30%, 40%, and 50%) and fermentation time (7 days, 9 days, and 11 days). Thebest chemical and organoleptic analysis based on the highest antioxidant activity was 50%pomegranate juice treatment and 9 days of fermentation time with 71,10% antioxidant activity,total phenol 9,04 GAE/L, reducing sugar 2,45%, total acid 1,35%, pH 3,1 , anthocyanin 53.52%,lightness (L*) 44.72 , redness (a*) 5.15, yellowness (b*) 2.57, fruity aroma 2.27, sour taste 2,85, andfor overall preference 3,49 for the treatment of adding 50% pomegranate juice and 9 days offermentation time. Pomegranate extract able to improve activity of antioxidant for kombucha.